Teori Penawaran dalam Ekonomi Islam - Iqra Mulhadi; Muhammad Albahi (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to describe the concept of supply from an Islamic economic perspective and what factors influence supply. This issue is important to study because economics in Islamic economics offers a more inclusive and just approach. And what factors influence the offer? This article's research method uses quantitative methods using literature review techniques. The results of this research show that in sharia supply analysis, maximum production efficiency is achieved when the sharia economic concept with profit sharing instruments is chosen compared to the use of interest instruments in conventional economics. This new discourse and discoveries that are much better both theoretically and practically will further strengthen the argument that Islamic economics is a better system.